ABC - Acid and Base Chemistry: An Android Mobile Learning Media to Improve Students’ Learning Outcomes and Motivation - Kaukaba, Syam Qeisha; Lutfi, Achmad (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
This research aimed to obtain